الازدواجية اللغوية في المجتمع الجزائري المجالات والأسباب - نايلي دواودة حمزة (Université de M'sila, 2020)
تتجسّد أهميّة المقال: في كونه يميط اللّثام عن اللغة المستعملة في المجتمع الجزائري ، بعد الكشف عن اللبس الحاصل بين مصطلحي الازدواجية والثنائيّة اللغويتين، اللتين تطبعان اللسان الجزائري، وأسبابهما، ومن ثمّة البحث عن الحلول لتجنب إصابة المؤسسات التعليمية بالدّاء الذي يعاني منه المجتمع (الحمام اللساني ) أو محاولة معالجته والتّقليل من أضراره إن وجد حقّا، وبالتّالي درءٌ لضرٍّ واقع، أو محتمل وقوعه في الأقسام التّعليميّة. The importance of the article is that it reveals the language used in Algerian society, after revealing the confusion between the terms duplicity and bilingualism, which characterize the Algerian tongue, and their causes, and hence search for solutions to avoid the infecting educational institutions to the suffering of the community (linguistic bath) or to try to treat it and reduce its harms if it really exists, and thus to prevent real harm, or potentially occurring in the educational departments
Keywords: الازدواجية اللغوية ، الثنائية اللغوية، اللغة ، المجتمع ، المتكلم . ; linguistic duality, bilingualism, language, society, speake